Effectiveness of message-framing intervention on complementary feeding related behaviors among mothers with infants aged 4-8 months: a 3-arm randomized controlled trial - Ziba Rafieyan-Kopaei; Zohreh Fathian-Dastgerdi; Mohammad Javad Tarrahi; Fereshteh Zamani-Alavijeh (BMC, 2019)
Abstract Objective Complementary feeding from the age of 6 months along with breastfeeding is essential for the health of infants. The effect of educational interventions on preventing the early or late onset of complementary feeding and correcting other relevant behaviors depends on the framing of educational messages. This study aimed to compare different types of message framing on maternal behaviors in complementary feeding of infants. Materials and methods This randomized controlled trial was performed on 96 mothers in three groups of 32 subjects with four-month-old infants in Isfahan (central Iran) during May-September 2018. Data were collected through self-report using a valid researcher-made questionnaire including demographic factors, knowledge, attitude, self-efficacy, and the complementary feeding related behaviors of mothers. For 4 months, the mothers received gain-framed messages in the GF group and loss-framed messages in the LF group from two different channels. The control group only received routine education. Data analysis was performed in SPSS20 using paired t-test, ANOVA, and Chi-square at the significance level of below 0.05. Results In this study, all three groups were matched in terms of demographic characteristics and mean scores of attitude, knowledge, and self-efficacy regarding the complementary feeding of their infants. Following the intervention, the mean knowledge score increased in all three groups and was more favorable in the intervention groups compared to the control group. However, no difference was observed between the GF and LF groups regarding their knowledge. In addition, the GF and LF groups were similar in terms of self-efficacy and behavior of mothers concerning the appropriate onset of complementary feeding. Meanwhile, the mean scores of attitude and behavior of mothers regarding the timely onset, diversity, and appropriateness of continuing complementary feeding were higher in the LF group compared with the GF group. Conclusion Framing messages changes the attitude and knowledge and improves behaviors related to complementary feeding. The interesting point is the different impacts of different types of framing on psychological and behavioral variables. In general, loss-framed messages have more effects on the attitude and certain parts of maternal behaviors. Trial registration IRCT, IRCT20180901040919N1. Registered 29 October 2018, https://en.irct.ir/trial/33782